Spellbound: Woman and Witchcraft in America - Reis, Elizabeth (Rowman & Littlefield Publishers, 1998)
Spellbound: Women and Witchcraft in America is a collection of twelve articles that explore crucial events in the history of witch-hunting and its demonization of women in American and American women's own use of witchcraft as a source of identity and strength, as well as the complicated relationship between the two. Beginning with the accused 'witches' of colonial America, Spellbound extends its focus through the nineteenth century to explore women's involvement with alternative spiritualities, and culminates with examinations of the contemporary feminist neopagan and Goddess movements.